The Gap in the National Leadership Recruitment Law By Post Reform Political Parties in Indonesia - Masduki, Mohammad (Constitutionale, 2023)
Democratic States generally elect a National Leadership to lead a State through the General Election process. In Indonesia itself, post-reform, to determine the position of replacing the National Leadership using the General Election system as stipulated in the constitution with the principles of direct, general, free, secret, honest, and fair which are held every 5 years. Before being elected, the National Leadership in Indonesia must be carried out by political parties in order to become the main spearhead of the people in a Democratic State. However, in determining candidates for National Leadership, it is necessary to carry out recruitment organized by political parties to adjust the vision and mission of political parties and according to the interests and needs of the people. However, there are legal loopholes in the recruitment process for political parties which will have legal ramifications for Indonesia's democratic system. This study uses a normative legal method, with a statutory approach and literature study. This study concludes that there were various legal loopholes contained in the Political Party Law which then collided with the System for Supporting National Leadership Candidates listed in the Election Law which resulted in a regradation of the nature of democracy in Indonesia. Therefore it is necessary to improve the legal loopholes contained in the Law on Political Parties and the Law on Elections to provide concrete improvements system in the recruitment and formation of National Leadership. Such improvement is necessary in an attempt to avoid instant with the hope of avoiding instant recruitment which in terms of national leadership results in the depravity of the state system and leads to a recruitment system that runs in accordance with democracy.